Cruciate Substituting Implants in Primary Total Knee Arthroplasty. (24th January 2022) - Volkmar, Alexander J.; Elrod, Robert; Vickery, Justin W.; Yang, Charlie C.; Polkowski, Gregory G.; Martin, J. Ryan
Abstract : The use of cruciate substituting (CS) total knee replacement has been increasing in popularity. There are numerous factors that have likely contributed to this expansion. The CS philosophy incorporates the ease of use commonly cited by advocates of the posterior stabilized (PS) total knee design with the bone preservation associated with a cruciate retaining (CR) design. The ultra-congruent highly cross-linked polyethylene liner increases stability without an appreciable change in wear. Furthermore, balancing the flexion and extension gaps does not require "titrating" the posterior cruciate ligament, improving the user-friendliness. This paper reviews the nuances of this implant design compared to PS and CR designs as well as provides surgical technique recommendations/considerations.